Challenges and opportunities for integrating traditional healing approaches with biomedical care for mental illness: A scoping review from healers’ perspectives - Alemayehu Molla Wollie; Kim Usher; Kylie Rice; Md Shahidul Islam (PLoS ONE, 2025)
Background A considerable number of people receive care from traditional healers for mental illness. Integrating traditional healing practices with modern treatment may improve the outcomes for people with the symptoms of mental illness. However, there has been limited joint efforts toward integration of the two approaches. Therefore, this review is intended to summarize the challenges and opportunities of integrating traditional treatment approaches with biomedical treatment for mental illness from the perspective of traditional healers. Methods Asksey and O’Malley’s framework and the Preferred Reporting Items for Systematic Review and Meta-Analysis Extension for Scoping Review (PRISM-ScR) guidelines were followed to conduct this scoping review. Searches of databases, including PubMed/Medline, PsycINFO, CINAHL, Scopus, and the Web of Sciences were conducted. Additionally, Google and Google Scholar were searched for other information, including grey literature. All articles published between January 2014 and June 2024 were considered. Themes and subthemes were created using Nvivo-12 software. A thematic synthesis was used to report the evidence. Result Based on the eligibility criteria, 54 of the 4071 initially identified articles were included. From the healers’ perspectives, governmental policy (guidelines, recognition, education, training, and financial issues), intellectual property issues, attitude, disease understanding differences, and referral are the major challenges for the integration of traditional healing approaches with biomedical treatment for mental illness. Healers’ willingness for integration, the effectiveness of the healing approaches, and the World Health Organization’s recognition of traditional healing are identified as enablers for integration. Conclusion Integrative work between traditional healing approaches and biomedical services presents an opportunity to assist in addressing the treatment gap for mental illness. This review presents a synthesis of the major challenges that hinder the integration of traditional healing approaches with biomedical care, and enablers that may facilitate integration. This review of the evidence can support policymakers and other stakeholders in reducing the major challenges of integration noted by healers and maximising opportunities for collaboration. The review also highlights the need to design culturally appropriate guidelines for integration and referral between the two systems.